The Relationship of Ambivalence towards Lecturers with University Students’ Psychological Distress and Mental Health - Herr, Raphael; Birmingham, Wendy C.; Deyerl, Veronika; Diehl, Katharina (Social Sciences, 2024)
Social interactions that are simultaneously characterized by positive and negative aspects—i.e., ambivalent relationships—have been found to be related to distress and poor mental health. As the university setting is also characterized by several social interactions, this study aimed to investigate for the first time to what extent objective and subjective ambivalence towards lecturers or instructors are linked to university students’ distress levels and mental health indicators. A notable relationship of ambivalence with the outcomes was found in 1105 students from Germany. The association with psychological distress was more pronounced for objective than for subjective ambivalence (adjusted betas = 0.342 vs. 0.261, p-values < 0.001), while both also had an independent association. The association with mental health was comparable for both types (adjusted beta = −0.206 vs. −0.191, p-values < 0.001). For paradoxical emotions, the relationship with objective ambivalence was stronger, and only this remained significant in the mutually adjusted model (adjusted beta = 0.376, p-value < 0.001). This study provided evidence of a previously unconsidered stressor at the university—ambivalence towards lecturers—associated with negative health effects among students. Future studies are needed to establish this connection and to create the basis for preventative measures.
CRIS-Team Scopus Importer:2024-11-01
Keywords: ambivalence; ambivalent social relationships; distress; mental health; paradoxical emotions; university students